Role of hospital environmental surfaces in the transmission of the severe acute respiratory syndrome - Coronavirus-2 - El-Masry, Eman A; Taha, Ahmed E (The Journal of Infection in Developing Countries, 2022)
Introduction: Severe acute respiratory syndrome - Coronavirus-2 (SARS-CoV-2) is mainly transmitted via respiratory secretions through coughing, sneezing, or contact with contaminated surfaces. This virus can be present in feces and many body fluids. The study aimed to screen the hospital environment as a potential source for SARS-CoV-2 transmission and identify the hospital zones with the highest contamination levels. Methodology: Swabs were collected from different sites in the hospital before and after routine cleaning/disinfection, transported in vials containing 1-3 mL of viral transport medium, and stored at -80 ℃ as soon as possible until the time of testing. The real-time reverse-transcription PCR (rRT-PCR) system targeting RNA-dependent RNA polymerase and E genes was used to detect the SARS-CoV-2 RNA. Results: Moderate environmental contamination by SARS-CoV-2 RNA was detected by rRT-PCR before routine cleaning/disinfection (52% of the swabs were positive). The hospital surfaces with the highest contamination levels were elevators’ buttons, sinks and faucets’ handles at the waiting rooms, patient’s room and bathroom, call buttons and telephones in the patient’s room, toilet bowl surface, the doorknob and light switches at the X-ray room, and the computer keyboard at the staffroom. All the swabs collected after routine cleaning/disinfection were negative for SARS-CoV-2 RNA by rRT-PCR. Conclusions: The hospital environment is a high-risk area that can be contaminated by SARS-CoV-2 through contact, respiratory, and maybe fecal shedding of the virus. To limit this fatal virus transmission, strict adherence to proper hand hygiene with frequent optimal decontamination of hospital environmental surfaces is essential.